Expanding Literature of Human Right to Life in Pakistan - Tahir Pervaiz Malik; Aman Ullah (بازیافت, 2018)
Right to life was incorporated in the Constitution of 1973, under Article 4 and 9. Initially, it was limited to be interpreted as a life limited to a vegetative life for a long time. However, progressive approach was adopted to give it new meanings in late 80’s.  Gradually, the judiciary stepped forward and started to widen the scope and vires of right to life, improving its quality. The constitutions which provide very rigid procedure for an amendment are big barriers to introduce new human rights like quality of life. It is the judiciary which provides a ray of hope by expanding horizons of already guaranteed constitutional rights. Resultantly, new rights emerged due to judicial role, raising standard of quality of life including right to shelter, right to livelihood/work, right to health, right to education, and right to protection of family, right to monitory compensation, right to go abroad and right to legal aid.